PERBANDINGAN TINGKAT NYERI PADA PASIEN POST SECTIO CAESAREA METODE KONVENSIONAL DAN ERACS DI RSIA MURNI TEGUH ROSIVA MEDAN - Sinaga, Dora Marthalena (STIKes Mitra Husada Medan, 2024)
Background: One of the common problems experienced by caesarean section patients is post-cesarean section pain in postpartum mothers. Post-cesarean section pain can have an impact in the form of limiting the movement of the attachment device, interference or even the inability to carry out daily activities that are highly dependent on the mother. Objective: To compare the level of pain in post-section caesarean patients with conventional and ERACS methods. Methods: This study is a quantitative study and a comparative design with a cross-sectional approach. The study was conducted at RSIA Murni Teguh Rosiva Medan. The population was 53 patients per month and the sample obtained was 48 people who were divided into 2 groups, so that each group consisted of 24 people. Sampling was by accidental sampling. The analysis was performed univariately in the frequency distribution table and bivariately using the Mann Whitney test because the data were not normally distributed. Results: This study showed that pain in post-cesarean section patients using the conventional method was in the moderate pain category (100.0%), or an average score of 4.79 ± 0.658, while pain in post-cesarean section patients using the ERACS method was in the mild pain category (91.7%), or an average score of 2.71 ± 0.624. There was a significant difference in the level of pain between post-cesarean section patients using the conventional method and post-cesarean section patients using the ERACS method (p = 0.000 <0.05). Conclusion: The pain felt by patients with cesarean section using the ERACS method was lighter than that of the conventional CS method. Suggestion: It is recommended that further researchers conduct further research on post-operative pain using therapies to overcome pain, namely deep breathing therapy, Benson relaxation therapy, and others.